A school takes on the school system: Resistance of the Akureyri Grammar School against novelties in the school legislation of 1946 - Kjartansson, Helgi Skúli (Menntavísindasvið Háskóla Íslands, 2016)
The article describes the intense reluctance with which the Akureyri Grammar School (i. Menntaskólinn á Akureyri, MA) in Iceland accepted a new school system being phased in around 1950. The new system gave the lower secondary schools (i. gagnfræðaskóli, cf. German/Scandinavian Realschule/realskole) a greatly increased role. Compulsory education, hitherto restricted to seven grades of elementary school, now included, on top of six initial grades, two years at the lower secondary level. The country’s two state run grammar schools, previously six grades after primary school, would henceforth be restricted to the four upper secondary grades, enrolling students who had passed a nationwide qualifying examination (i. landspróf) after three grades of lower secondary schooling. The place of the grammar schools in the new system was a modification of the practice already established in Reykjavík, the capital, where the grammar school, more prestigious than MA, had to deal with an increasing glut of applicants. It had strictly limited the numbers admitted to the lowest grades while admitting a majority of its students directly into its 3rd grade on the basis of a competitive examination, now replaced by the nationwide exam, thus allowing students from all parts of the country to compete on more equal terms. At MA, admissions had been much less strictly regulated. Some students were admitted after passing the annual entrance examination. But a larger number were admitted by the headmaster, acting on formal or informal references, and were allowed to start in any of the first three grades, even in midyear or just before exams. Such flexibility suited the needs of keen students growing up on farms or in villages who could study at home with limited instruction, economizing on costly upkeep in Akureyri. For MA itself, competing with the more prestigious Reykjavík school while serving a less populous catchment area, this flexibility was also a useful way to attract a sufficient number of students. Therefore the school tried ...